2020
DOI: 10.25186/.v15i.1704
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical approach of the mobilization of reserve compounds in germinating coffee seeds

Abstract: The endosperm of coffee beans is an important structure which is composed of different reserve compounds. In the present study, we followed anatomical features during the reserve mobilization of Coffea arabica L. cv 'Catuaí' seed samples, harvested at 20 different sites, after 0, 3, 6, 12, 24, 30 and 45 days of imbibition. Seed samples were properly stored for enzyme activity assessment and fixed in FAA solution (formaldehyde, acetic acid and ethanol, 1; 1; 18) and kept in ethanol 70% solution, for histochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…These authors identified ultrastructural modifications in the cotyledon epidermis correlated with haustorial function. Studies with species from other botanical families relate a similar pattern of reserve degradation through histochemical analysis (Carvalho et al, 2022;Ferreira et al, 2020;Mazzottini-dos-Santos et al, 2017;Oliveira et al, 2020) and biochemical quantifications (Carvalho et al, 2022;Mello et al, 2022;Bicalho et al, 2016). The values of starch and protein content found in this study are similar to those reported during the formation of V. reitzii seedlings (Corredor-Prado et al, 2016.…”
Section: Discussionsupporting
confidence: 80%
“…These authors identified ultrastructural modifications in the cotyledon epidermis correlated with haustorial function. Studies with species from other botanical families relate a similar pattern of reserve degradation through histochemical analysis (Carvalho et al, 2022;Ferreira et al, 2020;Mazzottini-dos-Santos et al, 2017;Oliveira et al, 2020) and biochemical quantifications (Carvalho et al, 2022;Mello et al, 2022;Bicalho et al, 2016). The values of starch and protein content found in this study are similar to those reported during the formation of V. reitzii seedlings (Corredor-Prado et al, 2016.…”
Section: Discussionsupporting
confidence: 80%
“…However, it is important to note that seeds harvested at immature stages may have slow and irregular germination. It may be due to the presence of fruits that are not fully formed, and with insufficient accumulation of reserves (Oliveira et al 2020). Variability also depends on seed size, physical quality, seed health, storage time, and materials (Anteneh et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our biochemical analyses confirmed that MLG is the main component of the cell wall to be degraded and it is reasonable to attribute the thinning of the endosperm cell wall to this mechanism. Again, thinning of cell walls throughout germination has been observed in many plants, such as in barley grains and coffee beans [ 41 , 42 ]. Opanowicz et al estimated that the cell wall thickness in the central endosperm of Brachypodium grain was about 4.4 µm, which is more than twice the thickness of the cell walls in the central endosperm of wheat grain [ 6 ].…”
Section: Discussionmentioning
confidence: 99%